Evaluation of Circular Buffer and Service Area Buffer Methods in Accessibility Analysis of Trans Metro Bandung Route 1 Based on GIS - Adibah, Fairuz; Saputra, Doddy Cahyadi; Sugasta, Hervian Handika; Parabi, Ashraf Dhowian; Santosa, Dimas Puji (Jurnal Teknik Sipil, 2025)
This study examines public transportation accessibility in Bandung, the capital of West Java Province, located at 107 °36' E and 6 °55' S, covering 167.31 square kilometers and characterized by a mountainous "bowl-shaped" topography. Trans Metro Bandung (TMB) operates an integrated network of five main corridors and two feeder routes to enhance urban mobility. Corridor 1, the longest route, spans approximately 20 kilometers from Cibiru Terminal in the east to Cibeureum Terminal in the west, passing through major roads and serving 86 bus stops distributed across educational, commercial, office, and residential areas. The study utilizes secondary spatial data, including Bandung"™s road network and bus stop locations from the Trans Metro Bandung. Administrative boundary data delineates the study area. Using GIS software, the research compares two accessibility measurement methods: the circular buffer, which creates fixed-radius catchment areas around stops, and the service area buffer, which calculates accessible areas based on the actual street network. Both buffer types are merged to remove overlapping areas, producing union buffers representing unique coverage zones. Accessibility indices are calculated based on the union buffers: the Ideal Stop-Accessibility Index (ISAI) measures the ratio of circular buffer coverage to the ideal corridor buffer; the Actual Stop-Accessibility Index (ASAI) measures the ratio of service area buffer coverage to the ideal; and the Stop Coverage Ratio Index (SCRI) compares service area coverage to circular buffer coverage. These indices prevent overestimation caused by overlapping buffers and provide a realistic assessment of transit stop accessibility. This study provides valuable insights for developing more accurate and sustainable public transportation strategies in Bandung and similar urban contexts.